Stromal derived factor‐1 and granulocyte‐colony stimulating factor treatment improves regeneration of Pax7−/− mice skeletal muscles. Issue 4 (3rd November 2015) - Kowalski, Kamil; Archacki, Rafał; Archacka, Karolina; Stremińska, Władysława; Paciorek, Anna; Gołąbek, Magdalena; Ciemerych, Maria A.; Brzoska, Edyta
Abstract: Background: The skeletal muscle has the ability to regenerate after injury. This process is mediated mainly by the muscle specific stem cells, that is, satellite cells. In case of extensive damage or under pathological conditions, such as muscular dystrophy, the process of muscle reconstruction does not occur properly. The aim of our study was to test whether mobilized stem cells, other than satellite cells, could participate in skeletal muscle reconstruction. Methods: Experiments were performed on wild‐type mice and mice lacking the functional Pax7 gene, that is, characterized by the very limited satellite cell population. Gastrocnemius mice muscles were injured by cardiotoxin injection, and then the animals were treated by stromal derived factor‐1 (Sdf‐1) with or without granulocyte‐colony stimulating factor (G‐CSF) for 4 days. The muscles were subjected to thorough assessment of the tissue regeneration process using histological and in vitro methods, as well as evaluation of myogenic factors' expression at the transcript and protein levels. Results: Stromal derived factor‐1 alone and Sdf‐1 in combination with G‐CSF significantly improved the regeneration of Pax7 −/− skeletal muscles. The Sdf‐1 and G‐CSF treatment caused an increase in the number of mononucleated cells associated with muscle fibres. Further analysis showed that Sdf‐1 and G‐CSF treatment led to the rise in the number of CD34+ and Cxcr4+ cells and expression of Cxcr7. Conclusions: Stromal derived factor‐1 and G‐CSF stimulated regeneration of the skeletal muscles deficient in satellite cells. We suggest that mobilized CD34+, Cxcr4+, and Cxcr7+ cells can efficiently participate in the skeletal muscle reconstruction and compensate for the lack of satellite cells.